(3JMaI GdfGSc HeG jMJGL Edjg ef GdefGScs
(3ChdgG (B:s
(3Cf GbjO dg eNJUQkG ai GdefGSc JPcQI hYhfkG Ydi eG CQGO jchf eMJhjkG Ydi eG hQO ai Pdc ef GdCPcGQ hSejJg PcQ aVd GdML hGdYeQI s
(3BNQgG (B:s
(3hef NUGFU gPg GdCeI Cfge jONdhf GdLfI bHd SGFQ GdCee hefgG hHGdLedI abO ENJUJ gPg GdCeI HeG de jYWjI ZjQgG JeJ s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV cdeGJgG HGdMeQI hGdRQbI YdjgG Jedc HGSe YHO GdQMef Hf YHO Gddg GdLjefis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs